Operator Drug- and Alcohol-Testing Across Modes - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2012)
TRB’s Commercial Truck and Bus Safety Synthesis Program (CTBSSP) Synthesis 23: Operator Drug- and Alcohol-Testing Across Modes explores practices used to deter drug and alcohol use among operators within the U.S. Department of Transportation’s (DOT’s) regulated community.The report includes a brief history of the transportation workplace drug- and alcohol-testing program, the general approach, the reasons for testing, some of the issues that impact the validity of the tests, and an outline of the specific regulations by mode.Some alcohol- and drug-testing statistics are presented in the report to help provide a sense of the scope of the program and of the prevalence of illegal alcohol and drug use among safety-sensitive employees.The report also highlights alternative strategies aimed at helping to deter illegal alcohol and drug use among employees.
Keywords: Transportation and Infrastructure

Ethical and Scientific Issues in Studying the Safety of Approved Drugs - Institute of Medicine (The National Academies Press, 2012)
An estimated 48 percent of the population takes at least one prescription drug in a given month. Drugs provide great benefits to society by saving or improving lives. Many drugs are also associated with side effects or adverse events, some serious and some discovered only after the drug is on the market. The discovery of new adverse events in the postmarketing setting is part of the normal natural history of approved drugs, and timely identification and warning about drug risks are central to the mission of the Food and Drug Administration (FDA). Not all risks associated with a drug are known at the time of approval, because safety data are collected from studies that involve a relatively small number of human subjects during a relatively short period. Written in response to a request by the FDA, Ethical and Scientific Issues in Studying the Safety of Approved Drugs discusses ethical and informed consent issues in conducting studies in the postmarketing setting. It evaluates the strengths and weaknesses of various approaches to generate evidence about safety questions, and makes recommendations for appropriate followup studies and randomized clinical trials. The book provides guidance to the FDA on how it should factor in different kinds of evidence in its regulatory decisions. Ethical and Scientific Issues in Studying the Safety of Approved Drugs will be of interest to the pharmaceutical industry, patient advocates, researchers, and consumer groups.
Keywords: Health and Medicine

Accelerating the Development of New Drugs and Diagnostics: Maximizing the Impact of the Cures Acceleration Network: Workshop Summary - Institute of Medicine (The National Academies Press, 2012)
Advances in technologies and knowledge are creating new avenues for research and opportunities for the discovery and clinical development of innovative therapies and diagnostics. However, despite these opportunities, only a small fraction of investigational products are successfully developed into cures and therapies that can be accessed by patients. One response to the ever-widening gap between the number and promise of basic scientific discoveries and the translation of those discoveries into therapies is a renewed emphasis on collaborative approaches among federal agencies, academia, and industry, all directed at the advancement of the drug development enterprise. The newly developed Cures Acceleration Network (CAN)-a part of the National Center for Advancing Translational Sciences (NCATS) within the National Institutes of Health (NIH)-has the potential to catalyze widespread changes in NCATS, NIH, and the drug development ecosystem in general. On June 4-5, 2012, the IOM Forum on Drug Discovery, Development, and Translation held, at the request of NCATS, a workshop-bringing together members of federal government agencies, the private sector, academia, and advocacy groups-to explore options and opportunities in the implementation of CAN. Accelerating the Development of New Drugs and Diagnostics: Maximizing the Impact of the Cures Acceleration Network: Workshop Summary summarizes the workshop.
Keywords: Health and Medicine

Genome-Based Therapeutics: Targeted Drug Discovery and Development: Workshop Summary - Institute of Medicine (The National Academies Press, 2012)
The number of new drug approvals has remained reasonably steady for the past 50 years at around 20 to 30 per year, while at the same time the total spending on health-related research and development has tripled since 1990. There are many suspected causes for this trend, including increases in regulatory barriers, the rising costs of scientific inquiry, a decrease in research and development efficiency, the downstream effects of patient expirations on investment, and the lack of production models that have successfully incorporated new technology. Regardless, this trajectory is not economically sustainable for the businesses involved, and, in response, many companies are turning toward collaborative models of drug development, whether with other industrial firms, academia, or government. Introducing greater efficiency and knowledge into these new models and aligning incentives among participants may help to reverse the trends highlighted above, while producing more effective drugs in the process. Genome-Based Therapeutics explains that new technologies have the potential to open up avenues of development and to identify new drug targets to pursue. Specifically, improved validation of gene-disease associations through genomics research has the potential to revolutionize drug production and lower development costs. Genetic information has helped developers by increasing their understanding of the mechanisms of disease as well as individual patients' reactions to their medications. There is a need to identify the success factors for the various models that are being developed, whether they are industry-led, academia-led, or collaborations between the two. Genome-Based Therapeutics summarizes a workshop that was held on March 21, 2012, titled New Paradigms in Drug Discovery: How Genomic Data Are Being Used to Revolutionize the Drug Discovery and Development Process. At this workshop the goal was to examine the general approaches being used to apply successes achieved so far, and the challenges ahead.
Keywords: Health and Medicine; Biology and Life Sciences

Forum on Drug Discovery, Development, and Translation: 2011 Annual Report - Institute of Medicine (The National Academies Press, 2012)
In 2011, there was a need for innovation across the biomedical science, policy, and business sectors. The National Academies’ Forum on Drug Discovery, Development, and Translation (the Forum) contributed to the conversation by hosting public workshops on envisioning a framework for a transformed clinical trials enterprise, and advancing the discipline of regulatory science. The Forum membership dedicated activities to global health concerns and neglected diseases, such as multidrug-resistant tuberculosis, and undertook efforts to better engage the public in the drug discovery and development enterprise. For more information, please see https://www.nationalacademies.org/our-work/forum-on-drug-discovery-development-and-translation.
Keywords: Health and Medicine

Facing the Reality of Drug-Resistant Tuberculosis in India: Challenges and Potential Solutions: Summary of a Joint Workshop by the Institute of Medicine, the Indian National Science Academy, and the Indian Council of Medical Research - Institute of Medicine (The National Academies Press, 2012)
An estimated 8.8 million people fell ill with tuberculosis (TB) in 2010 and 1.4 million died from the disease. Although antibiotics to treat TB were developed in the 1950s and are effective against a majority of TB cases, resistance to these antibiotics has emerged over the years, resulting in the growing spread of multidrug-resistant (MDR) TB. Due to challenges in timely and accurate diagnosis of drug-resistant TB, length and tolerability of treatment regimens, and expense of second-line anti-TB drugs, effectively controlling the disease requires complex public health interventions. The IOM Forum on Drug Discovery, Development, and Translation held three international workshops to gather information from local experts around the world on the threat of drug resistant TB and how the challenges it presents can be met. Workshops were held in South Africa and Russia in 2010. The third workshop was held April 18-19, 2011, in New Delhi, India, in collaboration with the Indian National Science Academy and the Indian Council of Medical Research. The aim of the workshop was to highlight key challenges to controlling the spread of drug-resistant strains of TB in India and to discuss strategies for advancing and integrating local and international efforts to prevent and treat drug-resistant TB. This document summarizes the workshop.
Keywords: Health and Medicine

Calibration of Rutting Models for Structural and Mix Design - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2012)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 719: Calibration of Rutting Models for Structural and Mix Design highlights proposed revisions to the Mechanistic–Empirical Pavement Design Guide (MEPDG) and software to incorporate three alternative rut-depth prediction models that rely on repeated load (triaxial) permanent deformation or constant height testing to provide the requisite input data.The report also suggests revisions to the MEPDG that would provide for revised coefficients for the original and alternative rut-depth transfer functions or prediction models derived from material properties measured in the laboratory and pavement performance data.
Keywords: Transportation and Infrastructure

Safe and Effective Medicines for Children: Pediatric Studies Conducted Under the Best Pharmaceuticals for Children Act and the Pediatric Research Equity Act - Institute of Medicine (The National Academies Press, 2012)
The Best Pharmaceuticals for Children Act (BPCA) and the Pediatric Research Equity Act (PREA) were designed to encourage more pediatric studies of drugs used for children. The FDA asked the IOM to review aspects of pediatric studies and changes in product labeling that resulted from BPCA and PREA and their predecessor policies, as well as assess the incentives for pediatric studies of biologics and the extent to which biologics have been studied in children. The IOM committee concludes that these policies have helped provide clinicians who care for children with better information about the efficacy, safety, and appropriate prescribing of drugs. The IOM suggests that more can be done to increase knowledge about drugs used by children and thereby improve the clinical care, health, and well-being of the nation's children.
Keywords: Health and Medicine

Strengthening a Workforce for Innovative Regulatory Science in Therapeutics Development: Workshop Summary - Institute of Medicine (The National Academies Press, 2012)
The development and application of regulatory science - which FDA has defined as the science of developing new tools, standards, and approaches to assess the safety, efficacy, quality, and performance of FDA-regulated products - calls for a well-trained, scientifically engaged, and motivated workforce. FDA faces challenges in retaining regulatory scientists and providing them with opportunities for professional development. In the private sector, advancement of innovative regulatory science in drug development has not always been clearly defined, well coordinated, or connected to the needs of the agency. As a follow-up to a 2010 workshop, the IOM held a workshop on September 20-21, 2011, to provide a format for establishing a specific agenda to implement the vision and principles relating to a regulatory science workforce and disciplinary infrastructure as discussed in the 2010 workshop.
Keywords: Health and Medicine

Ensuring Safe Foods and Medical Products Through Stronger Regulatory Systems Abroad - Institute of Medicine (The National Academies Press, 2012)
A very high portion of the seafood we eat comes from abroad, mainly from China and Southeast Asia, and most of the active ingredients in medicines we take originate in other countries. Many low- and middle-income countries have lower labor costs and fewer and less stringent environmental regulations than the United States, making them attractive places to produce food and chemical ingredients for export. Safe Foods and Medical Products Through Stronger Regulatory Systems Abroad explains that the diversity and scale of imports makes it impractical for U.S. Food and Drug Administration (FDA) border inspections to be sufficient to ensure product purity and safety, and incidents such as American deaths due to adulterated heparin imported from China propelled the problem into public awareness. The Institute of Medicine Committee on Strengthening Core Elements of Regulatory Systems in Developing Countries took up the vital task of helping the FDA to cope with the reality that so much of the food, drugs, biologics, and medical products consumed in the United States originate in countries with less-robust regulatory systems. Ensuring Safe Foods and Medical Products Through Stronger Regulatory Systems Abroad describes the ways the United States can help strengthen regulatory systems in low and middle income countries and promote cross-border partnerships - including government, industry, and academia - to foster regulatory science and build a core of regulatory professionals. This report also emphasizes an array of practical approaches to ensure sound regulatory practices in today's interconnected world.
Keywords: Food and Nutrition; Health and Medicine

Envisioning a Transformed Clinical Trials Enterprise in the United States: Establishing an Agenda for 2020: Workshop Summary - Institute of Medicine (The National Academies Press, 2012)
There is growing recognition that the United States' clinical trials enterprise (CTE) faces great challenges. There is a gap between what is desired - where medical care is provided solely based on high quality evidence - and the reality - where there is limited capacity to generate timely and practical evidence for drug development and to support medical treatment decisions. With the need for transforming the CTE in the U.S. becoming more pressing, the IOM Forum on Drug Discovery, Development, and Translation held a two-day workshop in November 2011, bringing together leaders in research and health care. The workshop focused on how to transform the CTE and discussed a vision to make the enterprise more efficient, effective, and fully integrated into the health care system. Key issue areas addressed at the workshop included: the development of a robust clinical trials workforce, the alignment of cultural and financial incentives for clinical trials, and the creation of a sustainable infrastructure to support a transformed CTE. This document summarizes the workshop.
Keywords: Health and Medicine

Public Engagement and Clinical Trials: New Models and Disruptive Technologies: Workshop Summary - Institute of Medicine (The National Academies Press, 2012)
Clinical trials provide essential information needed to turn basic medical research findings into patient treatments. New treatments must be studied in large numbers of humans to find out whether they are effective and to assess any harm that may arise from treatment. There is growing recognition among many stakeholders that the U.S. clinical trials enterprise is unable to keep pace with the national demand for research results. The IOM, along with the Mount Sinai School of Medicine, held a workshop June 27-28, 2011, to engage stakeholders and experts in a discussion about possible solutions to improve public engagement in clinical trials.
Keywords: Health and Medicine

Scientific Standards for Studies on Modified Risk Tobacco Products - Institute of Medicine (The National Academies Press, 2012)
Smoking-related diseases kill more Americans than alcohol, illegal drugs, murder and suicide combined. The passage of the Family Smoking Prevention and Tobacco Control Act of 2009 gave the FDA authority to regulate "modified risk tobacco products" (MRTPs), tobacco products that are either designed or advertised to reduce harm or the risk of tobacco-related disease. MRTPs must submit to the FDA scientific evidence to demonstrate the product has the potential to reduce tobacco related harms as compared to conventional tobacco products. The IOM identifies minimum standards for scientific studies that an applicant would need to complete to obtain an order to market the product from the FDA.
Keywords: Health and Medicine

Public Engagement on Facilitating Access to Antiviral Medications and Information in an Influenza Pandemic: Workshop Series Summary - Institute of Medicine (The National Academies Press, 2012)
Influenza pandemics overwhelm health care systems with thousands or hundreds of thousands of sick patients, as well as those worried they may be sick. In order to ensure a successful response to the patient swell caused by a pandemic, robust planning is essential to prepare for challenges public health officials may face. This includes the need to quickly distribute and dispense antiviral medications that can reduce the severity and duration of disease to large numbers of people. In response to a request from the Centers for Disease Control, the Institute of Medicine's Forum on Medical and Public Health Preparedness for Catastrophic Events held a series of workshops that explored the public's perception of how to facilitate access to antiviral medications and treatment during an influenza pandemic. To help inform potential strategies still in the development stages at the CDC, workshops were held in Fort Benton, Montana; Chattanooga, Tennessee; and Los Angeles, California during February and March 2012 to consider the usefulness of several alternative strategies of delivering antiviral medication to the public. Participants considered how the normal systems for prescribing and dispensing antiviral medications could be adjusted to ensure that the public has quick, safe, and equitable access to both potentially life-saving drugs and information about the pandemic and treatment options. This document summarizes the workshops.
Keywords: Health and Medicine

Integrating Large-Scale Genomic Information into Clinical Practice: Workshop Summary - Institute of Medicine (The National Academies Press, 2012)
The initial sequencing of the human genome, carried out by an international group of experts, took 13 years and $2.7 billion to complete. In the decade since that achievement, sequencing technology has evolved at such a rapid pace that today a consumer can have his or her entire genome sequenced by a single company in a matter of days for less than $10,000, though the addition of interpretation may extend this timeframe. Given the rapid technological advances, the potential effect on the lives of patients, and the increasing use of genomic information in clinical care, it is important to address how genomics data can be integrated into the clinical setting. Genetic tests are already used to assess the risk of breast and ovarian cancers, to diagnose recessive diseases such as cystic fibrosis, to determine drug dosages based on individual patient metabolism, and to identify therapeutic options for treating lung and breast tumors, melanoma, and leukemia. With these issues in mind and considering the potential impact that genomics information can have on the prevention, diagnosis, and treatment of disease, the Roundtable on Translating Genomic-Based Research for Health hosted a workshop on July 19, 2011, to highlight and identify the challenges and opportunities in integrating large-scale genomic information into clinical practice. Integrating Large-Scale Genomic Information into Clinical Practice summarizes the speaker presentations and the discussions that followed them. This report focuses on several key topics, including the analysis, interpretation, and delivery of genomic information plus workforce, ethical, and legal issues.
Keywords: Health and Medicine

Evolution of Translational Omics: Lessons Learned and the Path Forward - Institute of Medicine (The National Academies Press, 2012)
Technologies collectively called omics enable simultaneous measurement of an enormous number of biomolecules; for example, genomics investigates thousands of DNA sequences, and proteomics examines large numbers of proteins. Scientists are using these technologies to develop innovative tests to detect disease and to predict a patient's likelihood of responding to specific drugs. Following a recent case involving premature use of omics-based tests in cancer clinical trials at Duke University, the NCI requested that the IOM establish a committee to recommend ways to strengthen omics-based test development and evaluation. This report identifies best practices to enhance development, evaluation, and translation of omics-based tests while simultaneously reinforcing steps to ensure that these tests are appropriately assessed for scientific validity before they are used to guide patient treatment in clinical trials.
Keywords: Biology and Life Sciences; Health and Medicine

Genome-Based Diagnostics: Clarifying Pathways to Clinical Use: Workshop Summary - Institute of Medicine (The National Academies Press, 2012)
The sequencing of the human genome and the identification of associations between specific genetic variants and diseases have led to an explosion of genomic-based diagnostic tests. These tests have the potential to direct therapeutic interventions, predict risk or onset of disease, or detect residual disease. As research progresses and an increasing number of associations are found, further tests will be developed that can aid in providing personalized treatment options for patients. However, the adoption of genomic diagnostic tests by health care providers has been limited due to a lack of evidence regarding the clinical utility of many tests. Health funders and practitioners lack the data necessary to distinguish which tests can improve practice or the clinical settings in which tests will provide the greatest value. The Roundtable on Translating Genomic-Based Research for Health held a workshop in November 2010 to determine what evidence is needed and how it is viewed by different stakeholders in order to develop genomic diagnostic tests of clinical value. Genome-Based Diagnostics summarizes the presentations and discussions that took place throughout the workshop. Two presentations, in particular, sparked extensive discussion. One presentation proposed that all genomic diagnostic tests be reviewed and approved by the Food and Drug Administration. The other observed that venture capitalists are no longer investing substantially in the development of genomic diagnostic tests because of a lack of clarity surrounding regulatory and reimbursement pathways. Both presentations suggested the need for major changes in the systems used to develop, regulate, and reimburse genomic diagnostic tests. The report also presents the perspectives of different stakeholders in the development of genomic diagnostic tests. Each stakeholder group has a different set of needs and issues of importance, yet commonalities among them are apparent, such as the need to put patients and health outcomes at the center of discussion and action.
Keywords: Health and Medicine; Biology and Life Sciences

Tracking Radiation Exposure from Medical Diagnostic Procedures: Workshop Report - National Research Council (The National Academies Press, 2012)
The growing use of medical diagnostic procedures is correlated with tremendous and undeniable benefits in the care of most patients. However, it is accompanied by growing concerns about the risks associated with diagnostic computed tomography and other procedures that utilize ionizing radiation. A number of initiatives in radiation safety in medicine have taken place in the United States and internationally, each serving different purposes. Their ultimate goals are to provide higher quality clinical management of the patient and to ensure that reasonable steps are taken to keep the exposures as low as possible without compromising diagnostic efficacy. Tracking Radiation Exposure from Medical Diagnostic Procedures: Workshop Reports provides a summary of the presentations and discussions that took place during the December 8-9, 2011, workshop titled "Tracking Radiation Exposure from Medical Diagnostic Procedures." This workshop was organized by the Nuclear and Radiation Studies Board of the National Academy of Sciences and sponsored by the Centers for Disease Control and Prevention, the U.S. Food and Drug Administration, and the U.S. Department of Health and Human Services. This workshop report was authored by a six-member committee of experts appointed by the National Academy of Sciences. This committee brought together public health regulators, physicians, manufacturers, researchers, and patients to explore "why," "what," and "how" to track exposure from medical diagnostic procedures and possible next steps.
Keywords: Environment and Environmental Studies; Health and Medicine

Human Performance Modification: Review of Worldwide Research with a View to the Future - National Research Council (The National Academies Press, 2012)
The development of technologies to modify natural human physical and cognitive performance is one of increasing interest and concern, especially among military services that may be called on to defeat foreign powers with enhanced warfighter capabilities. Human performance modification (HPM) is a general term that can encompass actions ranging from the use of "natural" materials, such as caffeine or khat as a stimulant, to the application of nanotechnology as a drug delivery mechanism or in an invasive brain implant. Although the literature on HPM typically addresses methods that enhance performance, another possible focus is methods that degrade performance or negatively affect a military force's ability to fight. Advances in medicine, biology, electronics, and computation have enabled an increasingly sophisticated ability to modify the human body, and such innovations will undoubtedly be adopted by military forces, with potential consequences for both sides of the battle lines. Although some innovations may be developed for purely military applications, they are increasingly unlikely to remain exclusively in that sphere because of the globalization and internationalization of the commercial research base. Based on its review of the literature, the presentations it received and on its own expertise, the Committee on Assessing Foreign Technology Development in Human Performance Modification chose to focus on three general areas of HPM: human cognitive modification as a computational problem, human performance modification as a biological problem, and human performance modification as a function of the brain-computer interface. Human Performance Modification: Review of Worldwide Research with a View to the Future summarizes these findings.
Keywords: Conflict and Security Issues; Behavioral and Social Sciences

A Research Strategy for Environmental, Health, and Safety Aspects of Engineered Nanomaterials - National Research Council (The National Academies Press, 2012)
The nanotechnology sector, which generated about $225 billion in product sales in 2009, is predicted to expand rapidly over the next decade with the development of new technologies that have new capabilities. The increasing production and use of engineered nanomaterials (ENMs) may lead to greater exposures of workers, consumers, and the environment, and the unique scale-specific and novel properties of the materials raise questions about their potential effects on human health and the environment. Over the last decade, government agencies, academic institutions, industry, and others have conducted many assessments of the environmental, health, and safety (EHS) aspects of nanotechnology. The results of those efforts have helped to direct research on the EHS aspects of ENMs. However, despite the progress in assessing research needs and despite the research that has been funded and conducted, developers, regulators, and consumers of nanotechnology-enabled products remain uncertain about the types and quantities of nanomaterials in commerce or in development, their possible applications, and their associated risks. A Research Strategy for Environmental, Health, and Safety Aspects of Engineered Nanomaterials presents a strategic approach for developing the science and research infrastructure needed to address uncertainties regarding the potential EHS risks of ENMs. The report summarizes the current state of the science and high-priority data gaps on the potential EHS risks posed by ENMs and describes the fundamental tools and approaches needed to pursue an EHS risk research strategy. The report also presents a proposed research agenda, short-term and long-term research priorities, and estimates of needed resources and concludes by focusing on implementation of the research strategy and evaluation of its progress, elements that the committee considered integral to its charge.
Keywords: Environment and Environmental Studies; Health and Medicine